Future land‐use scenarios and the loss of wildlife habitats in the southeastern United States. Issue 1 (1st January 2015) - Martinuzzi, Sebastián; Withey, John C.; Pidgeon, Anna M.; Plantinga, Andrew J.; McKerrow, Alexa J.; Williams, Steven G.; Helmers, David P.; Radeloff, Volker C.
Abstract : Land‐use change is a major cause of wildlife habitat loss. Understanding how changes in land‐use policies and economic factors can impact future trends in land use and wildlife habitat loss is therefore critical for conservation efforts. Our goal here was to evaluate the consequences of future land‐use changes under different conservation policies and crop market conditions on habitat loss for wildlife species in the southeastern United States. We predicted the rates of habitat loss for 336 terrestrial vertebrate species by 2051. We focused on habitat loss due to the expansion of urban, crop, and pasture. Future land‐use changes following business‐as‐usual conditions resulted in relatively low rates of wildlife habitat loss across the entire Southeast, but some ecoregions and species groups experienced much higher habitat loss than others. Increased crop commodity prices exacerbated wildlife habitat loss in most ecoregions, while the implementation of conservation policies (reduced urban sprawl, and payments for land conservation) reduced the projected habitat loss in some regions, to a certain degree. Overall, urban and crop expansion were the main drivers of habitat loss. Reptiles and wildlife species associated with open vegetation (grasslands, open woodlands) were the species groups most vulnerable to future land‐use change. Effective conservation of wildlife habitat in the Southeast should give special consideration to future land‐use changes, regional variations, and the forces that could shape land‐use decisions.